Stable interface between anode materials and Li1.3Al0.3Ti1.7(PO4)3-based solid-state electrolyte facilitated by graphene coating. (1st November 2022) - Liu, Lei; Wang, Qiaohui; Jie, Zhihui; Ma, Jianli; Cui, Xuan; Xu, Guoli; Gu, Chengqian; Ma, Lei; Liu, Yong
Abstract: A graphene surface coating strategy (G@LATP), to modify and improve the interfacial characteristics between the Lithium Aluminum Titanium Phosphate (LATP) electrolyte and different anodes, such as Li metal and Si film has been proposed. As a result, the Li/Li symmetric cell with graphene coating modified LATP electrolyte exhibits excellent cyclic stability, even at large current densities of 0.5 mA·cm −2 and 1 mA·cm −2 . The modified Li/G@LATP/LiFePO4 solid-state full cell is delivering a discharge specific capacity of 136 mAh· g −1 after 200 cycles at a current density of 0.1 mA·cm −2, corresponding to a capacity retention of 86.1%. The graphene coating technique also led to improved cyclic stability in the Si/Si symmetric cell with modified LATP electrolyte at current densities of 0.1 mA·cm −2 and 0.3 mA·cm −2, with polarization voltages of 0.063 V and 0.27 V after cycling for 1000 h, respectively. Moreover, the Si/G@LATP/LiFePO4 full cell shows an outstanding discharge specific capacity of 161 mAh· g − 1 at its 2nd cycle, with a capacity retention of 92.9% after 200 cycles. These results show that graphene coating of the LATP electrolyte is a facile and effective method to improve the interfacial characteristics of Li/LATP and Si/LATP.